A production systems study - Allied Thread Co. - Salazar, Faye A.; Cruz, Rona K. Veron; Ragasa, Catherine G. (Diliman, Quezon City College of Engineering, 1995)
The primary aim of this study is to address the problem of high labor cost for cone make-up. The first step is to look into the present system in order to evaluate several parameters which can be considered in the analysis. The number of workers, standard production, practical allocation, twinhead required per day provide a measure for system capabilities and system potentials which could be used to design other alternatives. Computations for the mentioned parameters above after combining cone welding and cone make-up operations yield more favorable results most specifically in terms of quantitative considerations. Due to manufacturing companies' relentless efforts to achieve competitive status, a popular alternative is to consider automation. Two machines for automating cone make-up operation were considered based on their features, the L-type and the Shrink Machine. For easier analysis, cost comparison for the three alternatives plus the existing was performed based on 1995 values. Cost comparisons were also done based on the forecasted sales for 1996-1998, after which the Net Present Value of all costs were computed to provide a basis for quantitative decision-making. Before recommendations were made, another comparison of the 4 alternatives was performed this time taking into account qualitative factors. Based on the thorough evaluations made on all alternatives, the group recommended that Allied Thread Co. consider automating the cone make-up operation using the L-type machine.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems